Area Light Sources for Real-Time Graphics - Snyder, John (1996)
In an effort to extend the sorts of lightning models used in real-time computer graphics, this paper presents several area light source models, including Lambertian and Phong illumination from constant and cosine-falloff hemispherical light sources, constant subhemispherical light sources, and constant polygonal light sources. The subhemispherical lighting model can also be used to represent illumination from finite-distance spherical light sources. The models are not unduly more expensive than the simple point light source models, and are capable of real-time evaluation.